Spatial Price Discrimination - Hoover, Edgar M. (Review of Economic Studies, 1937)
Journal Article Spatial Price Discrimination Get access Edgar M. Hoover, Jr Edgar M. Hoover, Jr Michigan Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 4, Issue 3, June 1937, Pages 182–191, https://doi.org/10.2307/2967453 Published: 01 June 1937